Ministerial decree 392/2016 regarding the rules governing the disbursement of the increase in pension prescribed by law no 60/2016 = قرار وزاري رقم 392 لسنة 2016 بقواعد صرف زيادة المعاشات المقررة بالقانون رقم 60 لسنة 2016 - Egypt; The middle east library for economic services, translator. (2025)
Ministry of Social Solidarity decree no. 392 of the year 2016 regarding the rules governing the disbursement of the increase in pensions prescribed by law no. 60 of the year 2016 قرارات وزارة التضامن الاجتماعى قرار رقم 392 لسنة 2016 بقواعد صرف زيادة المعاشات المقررة بالقانون رقم 60 لسنة 2016